Clay Flocculation Effect on Microbial Community Composition in Water and Sediment - Chen, Chunyi; Pan, Gang; Shi, Wenqing; Xu, Feng; Techtmann, Stephen M.; Pfiffner, Susan M.; Hazen, Terry C. (Frontiers in Environmental Science, 2018)
Clay-based flocculation techniques have been developed to mitigate harmful algal blooms; however, the potential ecological impacts on the microbial community are poorly understood. In this study, chemical measurements were combined with 16S rRNA sequencing to characterize the microbial community response to different flocculation techniques, including controls, clay flocculation, clay flocculation with zeolite, and clay flocculation with O2 added zeolite capping. Sediment bacterial biomass measured by PLFA were not significantly altered by the various flocculation techniques used. However, 16S rRNA sequencing revealed differences in water microbial community structure between treatments with and without zeolite capping. The differences were related to significant reductions of total nitrogen (TN), total phosphorus (TP) and ammonia (NH4+) concentration and increase of nitrate (NO3-) concentration in zeolite and O2 loaded zeolite capping. The relative abundance of ammonia oxidizing bacteria increased fourfold in zeolite capping microcosms, suggesting zeolite promoted absorbed ammonia removal in the benthic zone. Zeolite-capping promoted bacteria nitrogen cycling activities at the water-sediment interface. Potential pathogens that are usually adapted to eutrophic water bodies were reduced after clay flocculation. This study demonstrated clay flocculation did not decrease bacterial populations overall and may reduce regulatory indicators and pathogenic contaminants in water. Zeolite capping may also help prevent nutrients from being released back into the water thus preventing additional algal blooms.